ON THE RESULTS OF THE PRESIDENTIAL ELECTION IN KYRGYZSTAN - KABULOV, Egamberdy (CENTRAL ASIA AND THE CAUCASUS, 2009)
By 18 May, 2009, 18 people had decided to run for president of the Kyrgyz Republic. Within five days, they were to submit all the necessary documents to the Central Elections Committee, gather at least 50,000 signatures in support of their candidacy, and pass a state language competency exam. At the beginning of the election campaign, there were six candidates left in the running: current present Kurmanbek Bakiev, the only candidate from the opposition, leader of the Social-Democratic Party A. Atambaev, leader of the Ak-Shumkar party T. Sariev, head of the NGO and NCO Association T. Umetalieva, leader of the Zhoomart movement N. Motuev, and well-known physician Zh. Nazaraliev. On voting day (23 July), the majority of the republic’s citizens voted for Kurmanbek Bakiev and he was re-elected president. It is commonly believed that there is a political standoff in Kyrgyzstan between the northern and southern clans or, to be more precise, families. This popular opinion, although it is not entirely true, does indeed reflect the actual state of affairs to some extent. First president Akaev is considered a “northerner,” while Bakiev is a “southerner.” Most of the posts in the current government and state institutions are occupied by southerners. It was presumed that Bakiev would gather most of the votes in the country’s south. And this is indeed what happened. In his birthplace (the Jalal-Abad Region), he received 78.2% of the votes, while in the Naryn Region (in the north) he only obtained 29.3%, that is, 2.5-fold less. The concepts of “northerner” and “southerner” apply exclusively to the indigenous Kyrgyz population among whom kinship ties are still preserved and for whom place of birth and affiliation with a particular family are of immense importance. It is very difficult for the non-Kyrgyz to find a niche for themselves in the power structures. For example, the first government formed by Bakiev was entirely made up of representatives of the titular nation. Amendments on not permitting other nationalities to occupy positions in the power structures were made to the constitutions adopted under Akaev and Bakiev. The provision on mandatory knowledge of the Kyrgyz language makes it impossible for the representatives of other nationalities to climb to the top. Whereas a person wishing to become a deputy used to be able to simply nominate himself, now he must play by the game rules and become a member of a particular party. And since all the members of political parties are Kyrgyz, it stands to reason that titanic efforts must be exerted for a person to distinguish himself among them and be nominated. Presidential and parliamentary elections have always been accompanied by attempts to play up to the non-Kyrgyz electorate. The government and opposition suddenly remember that other nationalities exist. Numerous promises and assurances of upholding the spirit of internationalism are heard, since almost 40% of the voters are non-Kyrgyz. But this time it was perfectly clear that Bakiev already had his victory in hand.